Nazariyat al-Hukm and masadir al-Shari`ah (the theory of law and the sources of the shari'ah) - Kayadibi, Saim; Omar, Raihanah (Association of Muslim Social Scientists, 2008)
On 17 October 2008, the Academy of Islamic Studies held its first seminar on Nazariyat al-Hukm and Masadir al-Shari`ah (NAZMAS1/2008) at the University of Malaya, Kuala Lumpur, Malaysia. We would like to thank all of the lecturers and students of the Department of Shari`ah and Law, especially Ahmad Hidayat Buang (dean of the Apium) and Siti Mashitoh bt Mahamood (head, Department of Shari`ah and Law), for their support and encouragement.